Effects of Subsurface Drip Irrigation on Water Consumption and Yields of Alfalfa under Different Water and Fertilizer Conditions. (3rd February 2021) - Cao, Xuesong; Feng, Yayang; Li, Heping; Zheng, Hexiang; Wang, Jun; Tong, Changfu
Abstract : A field experiment was conducted for the purpose of examining the effects of different combinations of water and fertilizer applications on the water consumption and yields of alfalfa under subsurface drip irrigation (SDI). The results showed that the jointing and branching stages were the key stages for alfalfa water requirement. The water consumption had varied greatly (from 130 to 170 mm) during the growth period of each alfalfa crop. The water consumption during the whole growth period was approximately 500 mm, and the maximum water consumption intensity was 3.64 mm·d -1 . The overall changes in water consumption and yields during the growth period of the alfalfa displayed trends of first increasing and then decreasing. The sensitivities of the yields to water changes were much higher than that of fertilizer. The water use efficiency (WUE) of the alfalfa was determined to range from 1.68 to 3.20 kg·m -3, and the rate of growth had ranged from 4.85% to 51.77%. The WUE and rate of growth of the alfalfa indicated the following trend: second crop > third crop > first crop. The results of frequency analysis based on the water-nitrogen-yield regression equation are the following: irrigation amounts of 142 165 mm and nitrogen application of 61 80 kg·hm -2 have a 95% probability of obtaining a hay yield of alfalfa of more than 11903 kg·hm -2 . These results suggest that SDI is a promising irrigation method, which can increase the WUE and hay yield of alfalfa under the condition of SDI within an appropriate amount of water and nitrogen fertilizer, and too low or too high water and nitrogen fertilizer will adversely affect the WUE and hay yield of alfalfa.